Acute pulmonary histoplasmosis related to occupational roofing: A case report of two brothers - Martin Gnoni; Timothy McCann; Adrian Riva-Moscoso; Fortunato Príncipe-Meneses; Diego Chambergo-Michilot (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: Histoplasma capsulatum is the cause of a prevalent fungal disease in certain regions in the United States of America, like Ohio and the Mississippi River. Its clinical manifestations range from asymptomatic to life-threatening diseases,according to the immune system. A definitive diagnosis is made by biopsy.Case report: Two middle-aged brothers presented with a nine-day history of severe progressive dyspnea. Both were living in Cincinnati, Ohio, and encountered bird droppings 7 days prior to symptoms while working on a roofing project. It should be mentioned that they were not wearing masks. After extensive testing, they were diagnosed with acute pulmonary histoplasmosis. Both were successfully treated with azole-derivative fungal therapy.Conclusion: This is the first case of histoplasmosis acquired through occupational exposure related to roofing and is unique given the two patients were siblings